2014
DOI: 10.1089/biores.2014.0018
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Fibronectin and Laminin Signaling Promote Highly Efficient Cardiac Differentiation of Human Embryonic Stem Cells

Abstract: Cardiomyocytes (CMs) differentiated from human embryonic stem cells (hESCs) are a promising and potentially unlimited cell source for myocardial repair and regeneration. Recently, multiple methodologies—primarily based on the optimization of growth factors—have been described for efficient cardiac differentiation of hESCs. However, the role of extracellular matrix (ECM) signaling in CM differentiation has not yet been explored fully. This study examined the role of ECM signaling in the efficient generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 71 publications
(62 reference statements)
0
29
2
Order By: Relevance
“…Our results are difficult to compare with earlier studies wherein approximation 23 37 and qualitative analyses 38 were used to identify the relative content of ECM supportive of cardiomyogenesis. In addition, most ex vivo work has occurred in 2D in vitro systems 3 24 36 and it is clear now that 2D and 3D culture regimes are quite distinct in terms of integrin engagement and associated cell fate signaling.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our results are difficult to compare with earlier studies wherein approximation 23 37 and qualitative analyses 38 were used to identify the relative content of ECM supportive of cardiomyogenesis. In addition, most ex vivo work has occurred in 2D in vitro systems 3 24 36 and it is clear now that 2D and 3D culture regimes are quite distinct in terms of integrin engagement and associated cell fate signaling.…”
Section: Discussioncontrasting
confidence: 70%
“…In addition, these three main effects (Col I, LN and FN) are used routinely but variably for cardiomyocyte differentiation protocols and are present in high volume fractions in the adult and developing heart 22 . Finally, we found that concentrations of ECM used in 2D culture 23 24 (as extrapolated for the 3D volume space) would be included in the resultant formulation. Since we hypothesized that the responses would not be linear when each factor was changed from 0 mg/mL (low or −) to 0.83 mg/mL (high or + ) in FEs, a center point formulation (000 in Table 1 ) was added.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of cardiac cell culture, the presence of laminin and fibronectin may be advantageous as these proteins have been shown to promote cell attachment and proliferation, 41 , 42 as well as the cardiomyogenic differentiation of human ASCs 43 and embryonic stem cells (ESCs). 44 …”
Section: Discussionmentioning
confidence: 99%
“…Sa et al have investigated the effect of fibronectin/laminin combinations on the differentiation of ESCs without using any induction molecule: they found out that fibronectin/laminin 70/30 caused the highest percentage of differentiation into CMs positive for Nkx2.5 and cTnI after 14 days culture time and proposed a mechanism based on integrin-mediated MEK/ERK signalling and direct cell-to-cell communication from distinct cells respectively expressing the laminin and fibronectin integrin receptors [ 95 ].…”
Section: Biomaterials For Guiding Cell Behaviourmentioning
confidence: 99%